Kehamilan Heterotropic Dengan Disertai Syok Hipovolumik - Mochamad Ma'roef (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2015)
Heterotropic Pregnancy With Accompanied Hypovolumic ShockBackground: Heterotopic pregnancy refers to a pregnancy that occurred simultaneously in two different implantation site. The majority occur in the fallopian tube. The exact cause s not clear, but the combination of multiple pregnancy with intrauterine and extrauterine pregnancy, a risk factor for all entities must be addressed.Case presentation: A female 34 year old 17 weeks pregnant, complaints of loss of consciousness, and before the patient complains of abdominal pain after a bowel movement. Experienced bleeding from vagina a week ago lasted for 4 days. Blood pressure 76/43 mmHg, heart rate 97 x / m, temperature 36.6 C, respiratory rate 24 x / m, SaO2 96% without O2. Loss of consciousness (delirium), looked anemic, distended abdomen, muscular defans +, tenderness +, pale, dry, and cold on the extrimities. Palpable lump in the labia majora dekstra. Laboratory tests obtained Hb 7, HCT 37, leukocytes: 10.400, Platelets 283,000, HBsAg negative, serum Cloride 105, 3.7 Serum Potassium, Sodium Serum 138, GDA 119, Diff count 4/1/80/11/4, LED 64 / 86.Discussion: A definitive diagnosis is heterotopic pregnancy. Management of the case was a laparotomy, with the condition of the intra-abdominal bleeding is massive enough. Report found that extrauterine and intrauterine pregnancy with differentgestational age. There was still a big question mark is how the intra and extra uterine pregnancy in differentgestational age.Conclusion: Diagnosis wasectopic pregnancy + G1 P0000 A000 19 weeks + IUFD + hypovolemic shock. Found the incidence of ruptured ectopic pregnancy occurs when the gestational age of 17 weeks, with the possibility that the gestational age between intra and ekstrauterine pregnancy is different.